Cross margin analysis and perception of smallholder cattle farmers using arc's cattle infrastructural facility scheme in Fetakgomo Municipality, Sekhukhune District of Limpopo Province - Mampane, Moshoene Samuel (My University, 2019)
Cattle herd productivity in the smallholder sector is generally low in South Africa (Mapiye et al., 2009) with cattle off-take rates being as low as 15% per annum (ARC, 2016). Among the leading causes of reduced productivity in smallholder herds is cattle mortality caused by diseases and parasites, especially ticks (Hesterberg et al., 2007). Ticks and the diseases they transmit have been identified as the major cause of widespread morbidity and mortality in cattle kept by smallholder farmers in the semi-arid areas of South Africa (Dold and Cocks, 2001; Mapiye et al., 2009) which results in poor animal welfare. Access to animal health infrastructure and technology can help reduce the problem of cattle diseases. The study was conducted to examine the impact of ARC’s Infrastructural Facility Scheme on the profitability of cattle farming and perceptions of smallholder cattle farmers. The study had four objectives; (i) to identify and describe the socio-economic characteristics of smallholder cattle farmers in Fetakgomo Municipality and Makhuduthamaga Municipality; (ii) to assess the perception of smallholder cattle farmers on the facilities provided by ARC in the study area; (iii) to determine and analyse the profitability of smallholder cattle farmers in the study area and (iv) to assess the effect of cattle farmers’ socio-economic characteristics on cattle farming profitability in the area. A total of 224 smallholder cattle farmers were interviewed, of which 124 farmers were beneficiaries and 100 were non-beneficiaries. The Purposive Sampling procedure was employed to determine the desired sample size in both the two Municipalities. The results showed that 55% of the smallholder cattle farmers were beneficiaries and 45% of the smallholder cattle farmers were non-beneficiaries out of the sample size. There were more male-headed households of the beneficiaries and more female-headed households of the non-beneficiaries. An analysis of the farmers’ socio-economic characteristics further showed that the majority of the smallholder cattle farmers prefer using family labourers or household labourers in their cattle farming. The results depict that beneficiaries of the Animal Health Wise Project used 76.2% of the family labour and 23.8% of hired labourers for beneficiaries whereas for the non-beneficiaries, it was v 68.7% of the family labour and 31.3% of hired labour. Using family labour helped in minimising costs of labour. Farmers were asked a set of Likert type scale questions about their perceptions on the project. The perception index score revealed that the smallholder cattle farmers had a negative perception of it as the index score was skewed to the left with the value being 0.428. Profitability was measured through Gross Margin Analysis. The Gross Margin Analysis revealed that the mean value of the total revenue and gross margin for the beneficiaries were bigger than non-participants. This was because beneficiaries tend to sell their cattle at a higher price compared to the non-participants. Furthermore, smallholder cattle farmers that are beneficiaries tend to use the infrastructure and through that, their cattle productivity is higher resulting in higher gross margin and total revenue compared to the non-participants. The Multiple Linear Regression Model was used to assess the effect of cattle farmers’ socio-economic characteristic on the gross margin of the farmers in the study area. The results revealed that only 3 variables were significant. The total herd size, project participation and access to the market were significant at 1% and all had a positive effect towards the gross margin. The study suggested that there should be more infrastructural facilities that are built in other municipalities. By so doing, smallholder cattle farmers will use the facilities to improve their herd productivity and also improve their cattle’s health status. It was also recommended that there should be some training based on the use of the cattle infrastructural facilities scheme so that farmers can use the facilities effectively. Key words: Smallholder Cattle Farmers, Perception, Animal Health Wise Project, Infrastructural Facilities.
Thesis (M.Sc. Agriculture (Agricultural Economics)) -- University of Limpopo, 2019
Keywords: Smallholder Cattle Farmers; Perception; Animal Health Wise Project; Infrastructural Facilities; Livestock